2013
DOI: 10.4149/gpb_2013064
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptors – target molecules for isoflavones in cancer chemoprevention

Abstract: Breast cancer is the most occurring type of cancer among women. In Slovakia, there are yearly diagnosed about 1900 new cases of this disease. Breast cancer treatment is very expensive, psychic stressful and in some cases ineffective. Therefore, it is essential to search for new and/or alternative methods for breast cancer treatment, since nuclear receptors are considered to be a central goal for maximizing treatment opportunities in breast cancer. Among natural ligands for estrogen receptors (ERα and ERβ), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that loss of RARβ is a common event in the development of malignant tumors, and the induction of RARβ expression suppresses cancer development ( 2 7 , 17 ). Increased expression of RARβ has been found to correlate with the clinical response to various retinoids ( 1 , 18 ); however, the molecular mechanism of RARβ in regulating sensitivity to chemotherapeutic agents is little known. A major problem in the treatment of human cancer is the lack of response of many tumors to chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that loss of RARβ is a common event in the development of malignant tumors, and the induction of RARβ expression suppresses cancer development ( 2 7 , 17 ). Increased expression of RARβ has been found to correlate with the clinical response to various retinoids ( 1 , 18 ); however, the molecular mechanism of RARβ in regulating sensitivity to chemotherapeutic agents is little known. A major problem in the treatment of human cancer is the lack of response of many tumors to chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Altered expression of nuclear retinoid receptors is associated with the malignant transformation of human cells ( 1 ). Retinoic acid receptor β (RARβ) belongs to the RAR superfamily and is frequently silenced during epithelial cell carcinogenesis, including those of the breast, lung, esophagus, pancreas, cervix and prostate ( 2 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tryptophanand UV photoproducts of tryptophan, metabolites of arachidonic acid, cAMP, heme metabolites such as bilirubin, biliverdin, indirubin are endogenous ligands for AhR (Medjakovic et al 2010;Novotna et al 2011). A well characterised family of natural AhR ligands are also isoflavones, which are organic compounds found in various species of the legume family, such as soy beans and in red clover (Wall et al 2012;Bialesova et al 2013). Isoflavones belong to the class of phytoestrogens because they have estrogenic and/or anti-estrogenic activity (Mittal et al 2014).…”
mentioning
confidence: 99%